The impact of acute reduction of continuous-flow left ventricular assist device support on cardiac and exercise performance. - Jakovljevic, D; George, R; Nunan, D; Donovan, G; Bougard, R; Yacoub, M; Birks, E; Brodie, D (2010)
BACKGROUND: The use of the HeartMate II continuous-flow left ventricular assist device (LVAD) improves survival, quality of life and functional capacity of patients with advanced heart failure. However, no study so far has shown the benefits of these devices for cardiac function during peak exercise. OBJECTIVE: To assess cardiac and exercise performance in patients implanted with the HeartMate II LVAD under two settings: (i) optimal device support and (ii) reduced device support. METHODS: Twelve patients implanted with a HeartMate II LVAD performed a graded cardiopulmonary exercise test with respiratory gas exchange and non-invasive (rebreathing) haemodynamic measurements. After a 4 h resting period, patients performed an additional cardiopulmonary exercise test with reduced LVAD support (pump speed was reduced from optimal 9000-9600 to 6000 revs/min). RESULTS: In response to reduced HeartMate II LVAD support, resting cardiac power output and cardiac output decreased by 21% and 13%, respectively. Also at reduced device support, peak exercise cardiac power output was 39% lower (1.40+/-0.50 vs 2.31+/-0.58 W; p<0.05), peak cardiac output 30% lower (8.6+/-2.5 vs 12.2+/-2.1 l/min; p<0.05) and mean blood pressure 13% lower (74.3+/-14.9 vs 85.4+/-15.4 vs mm Hg; p<0.05). Exercise capacity was also diminished with 23% lower peak oxygen consumption (14.1+/-5.3 vs 18.2+/-4.5 ml/kg/min; p<0.05) and an 18% shorter exercise duration (516+/-119 vs 628+/-192 s; p<0.05). CONCLUSION: It has been shown for the first time that the HeartMate II LVAD can confer both resting and peak cardiac functional benefits to patients with end-stage heart failure, thus improving exercise capacity.